PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS PROYEK BERVISI SETS BERORIENTASI CHEMO-ENTREPRENEURSHI BAGI PESERTA DIDIK SMA/MA (Journal of Innovative Science Education, 2014)
AbstrakBanyaknya lulusan SMA yang tidak melanjutkan akan mengakibatkan pengangguran, maka diperlukan pembelajaran yang dapat membekali keterampilan peserta didik. Tujuan penelitian ini adalah    SETS  - .Perangkat yang  , rencana pelaksanaan  pembelajaran,  bahan  ajar,  dan  project  worksheet.  Penelitian  ini merupakan  penelitian  pengembangan  dengan  subyek  penelitian  peserta  didik kelas XI IPA MAN Demak Tahun Ajaran 2013/2014. Fokus  yang diteliti dalam penelitian ini adalah hasil belajar kimia, minat wirausaha, dan respon peserta didik. Data yang diperoleh kemudian dianalisis menggunakan uji t-tes dan metode deskriptif  digunakan  untuk  mengetahui  minat  wirausaha  serta  respon  peserta didik. Berdasarkan hasil penelitian dapat disimpulkan   SETS berorientasi Chemo- entrepreneurship yang dikembangkan dapat meningkatkan hasil belajar dan minat wirausaha peserta didik.AbstractThe number of  senior high school graduates who do not continue their study will result in unemployment,there fore they need a learning that can equip for their future needs. The purpose of this study was to develop a learning model based on SETS visionary project orientating on Chemo-entrepreneurship for the students. The sets of equipment developed are syllabus, lesson plan, teaching materials, and project worksheet. This is are search development study. The subjects were the students of grade XI-Science of MAN Demak, the school year of 2013/2014. The focus examined in this studywasthe students’ of  chemistrylearning result, their interest in entrepreneurship, and their perception on the learning model. The data obtained were analysed by using t-test and the descriptive method was used to determine the students’interest in entrepreneurship as well astheirperception on the learning model. Based on the result of  this study,it wasconcluded that learning model based. Project that feature SETS vision and orientating on Chemo-entrepreneurship developed can improve the students’learning outcomesand interest in entrepreneurship, and receives a positive response from students.